The Expression and Significance of NLRP3 Inflammasome in Patients with Primary Glomerular Diseases - Jing Xiong; Yang Wang; Ning Shao; Pao Gao; Hui Tang; Hua Su; Chun Zhang; Xian-Fang Meng (Karger Publishers, 2015)
Background/Aims: Primary glomerulonephritis (PGN) is the most common reason inducing end stage renal disease in China, however, its pathogenesis remains unclear. The present study was designed to test the hypothesis that the formation and activation of NLRP3 (Nod-like receptor family pyrin domain containing 3) inflammasomes is an important initiating mechanism resulting in PGN. Methods: Serum samples and frozen sections were collected from 38 cases with PGN, and renal tissues were obtained from 22 of them. NLRP3 inflammasomes were detected by RT-PCR and immunofluoresence methods. The relationship between NLRP3 and clinical/pathologic indexes was analyzed. Results: RT-PCR analyses demonstrated that the mRNA levels of NLRP3 and caspase-1 genes were elevated significantly in renal tissues of PGN patients compared to those from normal pericarcinoma tissues. Moreover, the increased level of NLRP3 mRNA was correlative with a decrease in nephrin mRNA level and an increase in desmin mRNA level, which indicates that NLRP3 participates in podocyte injury in PGN patients. Immunofluorescence analysis also showed the protein expressions of NLRP3 and caspase-1 were increased in the glomeruli of PGN patients. Neverthless, there was no obvious regularity was presented in further subgroup analysis according to pathological types. In addition, increased NLRP3 was associated with the deterioration of renal function and glomerulosclerosis. IL-1β, a product of NLRP3 inflammasome activation, had a significant correlation with proteinuria. Conclusions: The formation and activation of NLRP3 inflammasomes in podocytes has been importantly implicated in the development of PGN-associated glomerular injury.